Meningkatkan Kemandirian Belajar Siswa Melalui Metode Discovery Learning Berbantuan Modul Materi Dialog di Fase F SMAN 1 Katingan Tengah - Gining Fustika Dewi; YL Sukestiyarno; Nursih Martadi (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The Discovery Learning learning method is an effort carried out by the teacher to make students more active and discover their own knowledge, experiences, related to the material provided by the teacher when learning takes place both in real classes and digital classes (Class Room). The aim is to train students to be active, skilled, brave, creative, and have the power to think critically and analytically in solving every problem that arises in their daily lives, especially in every lesson material provided. The Discovery Learning Method assisted by this Learning Module is applied to PAkat Phase learning. F, where all students are given the opportunity to share with their friends in groups and are responsible for carrying out each assignment given, and collecting each assignment on time. The increase in student activity and skills in cycle I to cycle II is seen to have increased, as evidenced by this, from an average percentage score of 75.% to an average score of 80.75 in cycle II and with 100% student attendance from cycle I to cycle II. Likewise with students' grades, the results of corrections from peers and the principal show an increase in changes in behavior and increased attendance, as well as increased student grades. From the results of these observations, the author believes that the Discovery Learning Method Assisted with Learning Modules has been proven to be able to improve student learning outcomes, especially in Catholic Religion lessons in Phase F, at SMAN 1 Katingan Tengah School. Improving speaking skills and analyzing questions, material in Catholic Religious Education lessons And Characteristics have increased and have a very strong influence on other subjects, and it is certain that students' apective, psychomotor and cognitive scores have increased satisfactorily. PAK and Competency test student scores are 100% above the KKM. In preparing this classroom action research report, the researcher is fully aware that there are still many shortcomings and errors in expressing ideas and sentences. Therefore, the author really hopes for suggestions and criticism that support improving subsequent research. Finally, the author hopes that this classroom action research can be useful for the development of the world of education in Indonesia, especially in Katingan Regency, Central Kalimantan Province.